Women's work. From pertmit to obligation - ARIAS, Patricia (Papeles de Población, 2018)
The aim of this article is to document and explain the reasons that have generated widespread and compulsory female labor from two perspectives: on one hand, as a result of job precarity, especially of male employment. On the other side, regarding sociodemographic and cultural changes, especially the reduction in the size of households, migration to the United States, the lack of, dissolution and shortening duration of unions; processes that have generated unforeseen situations in domestic residential groups that have triggered mandatory women’s work in the long term.